2005
DOI: 10.1093/eurpub/cki119
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of sexual harassment in Swedish high schools: experiences and school-environment problems

Abstract: Female high-school students in Sweden are exposed to a variety of inappropriate and/or unacceptable behaviours of a sexual nature, or based on sex, that may infringe their right to a supportive, respectful and safe learning environment or their dignity. Greater efforts are needed to analyse and prevent sexual harassment in schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 15 publications
2
34
0
3
Order By: Relevance
“…The prevalence of sexual harassment in the school was higher than the findings of study conducted in Canada where the prevalence rate was 23% [25][26][27]. Study conducted in Kenya on schools revealed that prevalence of sexual harassment in school was 60% which is inconsistent with the corresponding values of this finding [28].…”
Section: Discussionmentioning
confidence: 71%
“…The prevalence of sexual harassment in the school was higher than the findings of study conducted in Canada where the prevalence rate was 23% [25][26][27]. Study conducted in Kenya on schools revealed that prevalence of sexual harassment in school was 60% which is inconsistent with the corresponding values of this finding [28].…”
Section: Discussionmentioning
confidence: 71%
“…The study group largely comprised students in the second year of Swedish high school (corresponding to 11th grade). For more detailed analysis of the sampling and administrative methods employed see Witkowska and Menckel (2005).…”
Section: Methods Study Group and Data Collectionmentioning
confidence: 99%
“…Schools function as integral parts of communities, and have to address violence to children as a result of gang culture (Khouri-Kassabri, Benbenishty, Asttor, & Zeira, 2004), other sub-cultural influences that might harm children (Witkowska & Menckel, 2005), poverty (Barnes, Belsky, Broomfield, & Melhuish, 2006) and structural issues relating to absence of amenities or housing (Anderson, Case, & Lam, 2001). Exploration of differences between neighbourhoods within individual country settings is important, as discrepancies between one location and another can themselves be a trigger for violence that implicates children (Currie et al, 2004).…”
Section: Causementioning
confidence: 99%